32 Examining the key factors impacting on the implementation of an educational program on constipation in specialist palliative care. Issue 3 (1st September 2018) - McIlfatrick, S; Muldrew, DHL; Carduff, E; Clarke, M; Coast, J; Finucane, A; Graham-Wisener, L; Hasson, F; Larkin, P; MacArtney, J; McCorry, N; Slater, P; et al.
Abstract : Introduction: Constipation is one of the most common symptoms in patients in specialist palliative care (SPC) settings and can cause considerable physical psychological and social suffering for the patient and their family. Due to the high variability in constipation assessment and management in SPC settings questions exist around how to implement an educational program in practice to address this clinical gap. Aim: To develop and test the feasibility and acceptability of a novel educational intervention for HCPs to manage constipation experienced by people in SPC settings. Method: Using the MRC framework for complex interventions and guided by the consolidated framework for implementation research an online resource was developed considering the content context and processes for implementation. Results: Assessment prevention and management were identified as the core aspects. Six sessions with theoretical content application to practice and reflection through interacting with colleagues were developed in line with the best available evidence. Incentives including an educational bursary and alignment with revalidation and support from senior management champions and the research team were identified as key elements needed successful implementation. Funding IT infrastructure and attitudes to the content have been flagged as potential barriers to success. Conclusion: A six week blended program covering the key concepts for assessment and management of constipation in palliative care has been created. Content evidence from the literature and empirical data on the preferred structure and method of delivery as well as key considerations of the contextual factors have been identified as key factors for implementation. References: . Craig P, et al . Developing and evaluating complex interventions: The new medical research council guidance. BMJ Clinical Research Ed 2008;337(October):a1655. Available at: http://discovery.ucl.ac.uk/168426/ . Damschroder LJ, et al. Fostering implementation of health services research findings into practice: A consolidated framework for advancing implementation science. Implementation Science2009;4(50). . Friedrichsen M, Erichsen E. The lived experience of constipation in cancer patients in palliative hospital-based home care. Int J Palliat Nurs [Internet] 2004;10(7):321–5. Available from: http://search.ebscohost.com/login.aspx?direct=true&profile=ehost&scope=site&authtype=crawler&jrnl?=13576321&AN=13991056&h=XKMF4r08srZuhDY0j7C95oLLyYKNHUcvoeEuhyXNnsIM2BI%2BEhmcY1pPP%2BN1pvrMzQ9Bn9b5j45X6WzyBRydEA%3D%3D&crl=c [Accessed: 2017 August 21] . Tvistholm N, Munch L, Danielsen AK. Constipation is casting a shadow over everyday life? A systematic review on older people's experience of living with constipation [Internet]. Journal of Clinical Nursing2017;26:902–14. Available from: http://doi.wiley.com/10.1111/jocn.13422 [Accessed: 2017 August 21]